Teaching the history of psychology in the university Paraguay - García, José E. (2011)
In Paraguay the teaching of the history of psychology began with the foundation of the first psychological department in the decade of 1960 at the Catholic University in Asunción. That first course were named History of psychological systems and the professor was the uruguayan jesuit priest Carlos Mullin. The first experiences were courses of general history of psychology that paid little attention to both the latin american and the paraguayan psychologies. The organized study of this last one began with the regular course in the History of Psychology at the Catholic University in Ciudad del Este (1994) that gathered particular information concerning the paraguayan national psychology. In 2004 a seminary named Introduction to Paraguayan Psychology was organized at the University of the North in Asunción, including a special segment on the History of Psychology in Paraguay. This article describes in chronology the teaching of the history of psychology in the country as a matter of specific contents on psychology study programs. In this paper a clear difference between the general courses in the history of psychology that comprises special contents on paraguayan psychology and the courses oriented toward psychology in Paraguay as its main academic content is proposed. The article also discusses both the general characteristics of these courses and the thematic axis for their teaching, the contents for the study of the field and other aspects, as well as its relevancy for the training of psychologist in Paraguay.